2021
DOI: 10.1136/bmjopen-2020-044070
|View full text |Cite
|
Sign up to set email alerts
|

Detection of subclinical rheumatic heart disease in children using a deep learning algorithm on digital stethoscope: a study protocol

Abstract: IntroductionRheumatic heart diseases (RHDs) contribute significant morbidity and mortality globally. To reduce the burden of RHD, timely initiation of secondary prophylaxis is important. The objectives of this study are to determine the frequency of subclinical RHD and to train a deep learning (DL) algorithm using waveform data from the digital auscultatory stethoscope (DAS) in predicting subclinical RHD.Methods and analysisWe aim to recruit 1700 children from a group of schools serving the underprivileged ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…MS was the second most common lesion of which 7.0% had mild, 8.1% had moderate, and 55.8% had severe ( 13 ). The reported prevalence of RHD in Pakistan was found to be 22/1,000 in school-going children ( 14 ). Studies in Bangladesh, India, and Pakistan showed that the common non-clinical predictors of RHD were age, gender, living place, family size, number of people sharing a living room, wall material used in the home, number of siblings, and maternal occupation ( 4 , 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…MS was the second most common lesion of which 7.0% had mild, 8.1% had moderate, and 55.8% had severe ( 13 ). The reported prevalence of RHD in Pakistan was found to be 22/1,000 in school-going children ( 14 ). Studies in Bangladesh, India, and Pakistan showed that the common non-clinical predictors of RHD were age, gender, living place, family size, number of people sharing a living room, wall material used in the home, number of siblings, and maternal occupation ( 4 , 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…The limitations of objective performance data have restricted wide acceptability so far [ 90 , 91 , 92 ]. The auscultatory findings of CHD are integral to the clinical diagnosis and have the benefit of being a low-cost tool, but are subject to clinical expertise, which becomes a limitation in resource-limited countries and creates a need for support to the clinician [ 93 , 94 , 95 , 96 ] that is objective and reportable by even peripheral health workers. The lack of trained cardiologists at the peripheral level leads to an unavoidable miss of a timely clinical diagnosis of CHD, contributing to delayed intervention and thus a poor prognosis [ 97 ].…”
Section: Resultsmentioning
confidence: 99%
“…Further developments toward a more pragmatic uptake of echocardiographic screening in LMICs have included: (a) development of hand-held echo devices which are less expensive, generate smaller and shareable file sizes, and have a smaller profile without reliance on wired electricity [51]; (b) task-shifting of echo image acquisition, from highly trained cardiologists and echocardiographers to non-expert health care workers (HCW) with limited training, allowing for expansion of screening capabilities; (c) supportive cloud-based telemedicine programs for remote echo image interpretation; and finally, (d) expanding technological advances [54,55], with several companies now offering artificial intelligence guidance technology built into hand-held devices, thus empowering novice operators to perform screening echoes even after only minimal training, and promising deep learning approaches for automated flagging of abnormalities in the near future [56]. There is also ongoing effort to improve and simplify the WHF criteria for the diagnosis of latent RHD [57], with additional development of risk scores to predict outcomes in both borderline and definite latent RHD [57].…”
Section: Screening Echocardiography (Echo)mentioning
confidence: 99%